(untitled) (Research, Society and Development, 2020)
This study aimed to characterize the epidemiological profile of patients with hepatitis C assisted by the specialized component of Pharmaceutical Care in Teresina, Piauí, in 2018. This is a cross-sectional, observational study with a qualitative and quantitative approach, developed in Brazil. Specialized Component of Pharmaceutical Assistance in Teresina, Piauí, in 2019. The data collected refer to a sample of 100 processes. After the analysis, the information was recorded in the forms, and later in a spreadsheet, where the analysis procedure was performed through statistics. In this group, the average age was 57.9 years, with a higher prevalence of the age group. from 50 to 68 years old (63%), male (57%), mixed race (57%) and individuals with type 1 genotype (40.40%). The most commonly used regimen is Daclastavir + Sofosbuvir (40%) and the most common treatment line was 12 weeks (83%). The vast majority (93%) do not have any coinfection, but the most frequent coinfection in the sample is caused by the Human Immunodeficiency Virus (HIV). Most of the results found are in accordance with the literature. There are few studies about Hepatitis C in Brazil, considering this situation, it is considered important to know the prevalence of Hepatitis C, to raise awareness of the transmission pathways, as well as its symptoms, since it is a silent infection and can progress to chronicity, and on the effectiveness of the existing treatment, which is offered by the Unified Health System.